The transcriptional coactivator Eya1 exerts transcriptional repressive activity by interacting with REST corepressors and REST-binding sequences to maintain nephron progenitor identity. Issue 18 (21st September 2022) - Li, Jun; Cheng, Chunming; Xu, Jinshu; Zhang, Ting; Tokat, Bengu; Dolios, Georgia; Ramakrishnan, Aarthi; Shen, Li; Wang, Rong; Xu, Pin-Xian
Abstract: Eya1 is critical for establishing and maintaining nephron progenitor cells (NPCs). It belongs to a family of proteins called phosphatase-transcriptional activators but without intrinsic DNA-binding activity. However, the spectrum of the Eya1-centered networks is underexplored. Here, we combined transcriptomic, genomic and proteomic approaches to characterize gene regulation by Eya1 in the NPCs. We identified Eya1 target genes, associated cis -regulatory elements and partner proteins. Eya1 preferentially occupies promoter sequences and interacts with general transcription factors (TFs), RNA polymerases, different types of TFs, chromatin-remodeling factors with ATPase or helicase activity, and DNA replication/repair proteins. Intriguingly, we identified REST-binding motifs in 76% of Eya1-occupied sites without H3K27ac-deposition, which were present in many Eya1 target genes upregulated in Eya1 -deficient NPCs. Eya1 copurified REST-interacting chromatin-remodeling factors, histone deacetylase/lysine demethylase, and corepressors. Coimmunoprecipitation validated physical interaction between Eya1 and Rest/Hdac1/Cdyl/Hltf in the kidneys. Collectively, our results suggest that through interactions with chromatin-remodeling factors and specialized DNA-binding proteins, Eya1 may modify chromatin structure to facilitate the assembly of regulatory complexes that regulate transcription positively or negatively. These findings provide a mechanistic basis for how Eya1 exerts its activity by forming unique multiprotein complexes in various biological processes to maintain the cellular state of NPCs.